KETIKA MOHAMMED ARKOUN MEMBINCANG WAHYU - el-Mawa, Mahrus (ULUL ALBAB Jurnal Studi Islam, 2007)
Expressing of somebody's thought is like open a window of ideas world on a period. Terminology of "wahyu" or revelation in Qur'anic studies, then; often only concentrated on its subject in a past. Hence, impress that researchers less express revelation in modern perspective of science, such as linguistics, anthropology, and so on. Mohammed Arkoun is one among recent thinker of moslem trying to discuss about revelation. In the context of Islamic thought, Arkoun's contribution enough means to open the door of discourse on recent Islamic science. In this article can be known that how Arkoun in reading of revelation has a new perspective.